Iodixanol supplementation in freezing extender improves the antioxidant capacity of semen - Marqui, Fernanda N. [UNESP]; Martins, Alicio [UNESP]; da Cruz, Tairini Erica [UNESP]; Berton, Tatiana Issa Uherara; de Paula Freitas-Dell’Aqua, Camila [UNESP]; Dell’Aqua, José A. [UNESP]; Oba, Eunice [UNESP] (Wiley, 2023)
The aim of this study was to evaluate the effect of supplementing bovine semen freezing extender with different concentrations of iodixanol on post-thaw sperm characteristics. Six ejaculates of three Nellore bulls were pooled and diluted in commercial extender (BotuBov®) and then divided into 4 groups: control group (without adding iodixanol); groups G1.5, G3, or G6 according to the concentration of iodixanol solution (RedCushion®). After dilution, the samples were cooled and frozen. Post-thaw semen evaluation included sperm motility by CASA immediately after thawing and after 60 min of incubation at 37°C, flow cytometry analysis for integrity of plasma and acrosomal membranes, membrane destabilization and translocation of phosphatidylserine, mitochondrial membrane potential, and formation of intracellular anion superoxide ((Formula presented.)), hydrogen peroxide (H2O2), and membrane lipid peroxidation. The group G6 presented significantly higher (p <.05) total and progressive motility, percentage of plasma and acrosomal membrane integrity, and H2O2 than control and group G1.5. Furthermore, group G6 showed lower (p <.05) lipid peroxidation than control. In addition, regardless of the concentration used, the percentage of spermatozoa without phosphatidylserine translocation was higher (p <.05) in all iodixanol supplemented groups. In conclusion, iodixanol supplementation preserved the motility and integrity of sperm membranes during cryopreservation and protected against lipid peroxidation.
Keywords: antioxidant; BotuBov®; Cryocapacitation; RedCushion®; spermatozoa